The mechanochemical activation study of Tsagaan-tsav zeolite - Zolzaya, Ts; Davaabal, B; Ochirbat, Z; Oyun-Erdene, G; Minjigmaa, A; Temuujin, J (Mongolian Journal of Chemistry, 2014)
Characterisation of mechanochemically activated Tsagaan-tsav zeolite has been performed. Tsagaan-tsav zeolite has been activated with a vibration mill for 2, 3, 5, 10 and 20 minutes. Ball to powder ratios were varied 1:10, 1:20, 1:50 and 1:100. Efficiency of milling determined based on amorphisation rate and cation exchange capacity changes. The highest efficiency was obtained for zeolite milled with ball to powder ratio of 100. Structural characterisation was performed with XRD, SEM, BET and particle size analyzer. Mechanochemical activation improves cation exchange capacity of natural zeolite. DOI: http://dx.doi.org/10.5564/mjc.v12i0.181 Mongolian Journal of Chemistry Vol.12 2011: 98-101